Sustainable overall social transformation as a way of progress. (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
The paper concerns the fundamental issues of the sustainable social progress. As follows from the argumentation, a realistic design of institutional changes in connection with resource and organizational changes needed for sustainable progress is called for to realize in the line of overall social system transformation. This approach presupposes an exhaustive study of interconnected transformations in the main societal fields as system processes considering the influence of relatively exogenous factors (technological, demographic and climate changes). In turn, it is advisable, taking in view current world challenges, to expose an idea of ​​universal sustainability, the property of which is inherent in all social practices, and not just mediating the relationship between society and its environment. The first result of study concludes in revealing the fundamentals of overall social system sustainability. The second result: the transition to sustainable transformation of society supposes the synergetic implementation of structure-forming system and policy-driven shifts.